THE INFLUENCE OF PRODUCT, PRICE, AND LOCATION ON STUDENTS' DECISIONS IN CHOOSING HIGHER EDUCATION INSTITUTIONS: A STUDY OF UNIVERSITIES WITH "GOOD" ACCREDITATION IN BANDUNG - Muhamad Wahyu Wicaksono; Ezra Karamang; Iqbal Insanul Kamil (Branding: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of product, price, and location on students’ decisions in choosing higher education institutions accredited as “Good” in Bandung. A quantitative approach with multiple linear regression analysis was employed. The findings reveal that, partially, only the product variable has a positive and significant effect on students’ decisions, while price and location have no significant influence. Simultaneously, the three variables significantly affect students’ decisions, explaining 47.9% of the variance, while the remaining 52.1% is influenced by other factors outside the research model. These findings indicate that educational product quality, including lecturers, academic services, facilities, and graduate career prospects, is the main consideration in institutions selection. Therefore, universities should prioritize improving educational service quality to enhance competitiveness.